2003
DOI: 10.1016/s0140-6736(03)14962-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a SARS-associated coronavirus vaccine in monkeys

Abstract: The causative agent of severe acute respiratory syndrome (SARS) has been identified as a new type of coronavirus. Here, we have investigated the ability of adenoviral delivery of codon-optimised SARS-CoV strain Urbani structural antigens spike protein S1 fragment, membrane protein, and nucleocapsid protein to induce virus-specific broad immunity in rhesus macaques. We immunised rhesus macaques intramuscularly with a combination of the three Ad5-SARS-CoV vectors or a control vector and gave a booster vaccinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
246
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(256 citation statements)
references
References 5 publications
8
246
0
2
Order By: Relevance
“…Although SARSCoV infection of humans has been contained through effective infection-control measures, resurgence is still a threat due to the presence of animal reservoirs (12). Consequently, several vaccines have been urgently developed (21)(22)(23). Studies of the immune response to coronaviruses suggest that both humoral and cellular immunity contribute to protection (61)(62)(63)(64).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although SARSCoV infection of humans has been contained through effective infection-control measures, resurgence is still a threat due to the presence of animal reservoirs (12). Consequently, several vaccines have been urgently developed (21)(22)(23). Studies of the immune response to coronaviruses suggest that both humoral and cellular immunity contribute to protection (61)(62)(63)(64).…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the lack of identified SARS-CoV-specific CTL epitopes, the role of CTLs in immunopathogenesis and their function in viral clearance remain unclear. In addition, with the recent development of several vaccines against SARS-CoV, there is currently a need for a reliable markers to indicate effective SARS-CoV T cell responses (21)(22)(23). Hence, the identification of specific CTL epitopes should be of great use for both understanding viral control mechanisms and SARS vaccine evaluation.…”
mentioning
confidence: 99%
“…Recombinant modified vaccinia Ankara (MVA) virus expressing SARS-CoV S protein was immunogenic and protective in rodent and primate models (15)(16)(17); however, one group found that the MVA/SARSCoV S-immunized ferrets developed hepatitis upon challenge with SARS-CoV (17). Vaccine constructs based on replication defective human adenovirus type 5 expressing a partial or full-length SARSCoV S protein have been evaluated for immunogenicity in rats and monkeys (18,19), but immunization depends on a high vaccine dose, and safety and protective efficacy remain to be demonstrated. We previously used an attenuated version of human parainfluenza virus type 3, a common pediatric respiratory pathogen, to express the SARS-CoV S protein and showed that a single intranasal (i.n.)…”
mentioning
confidence: 99%
“…N onhuman primate models, including cynomolgus and rhesus macaques, represent an important tool for the development and validation of vaccine models and for the evaluation of immune responses to a considerable list of human pathogens including not only simian immunodeficiency virus/HIV chimera (SHIV), 4 but also severe acute respiratory syndrome-coronavirus (SARS-CoV), measles virus, monkeypox virus, Plasmodium falciparum, hepatitis B, C, and E viruses, and anthrax (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). With respect to the correct identification of the different protective elements that concur to immune protection after vaccination, recent evidences suggest that the evaluation of NK cell function could provide interesting and useful information in adaptive immune responses (15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%